E-Ticketing Application - M Iffan; W Yuniasari (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this paper is to determine and to discover the influence of the use of online ticket booking applications in the increasing number of passengers and the increasing business profits by making a comparison between tickets purchase online and offline. The method used was descriptive and survey, where the population taken in this study were customers working as workers, college students, and housewives. The results of this study were online ticket booking applications are suitable channel to increase the number of tickets purchase and profits.